Case report: Tibial nerve damage due to baker's cyst aspiration - Şahin, Mustafa (Springer London Ltd., 2019)
[Abstract Not Available]
Conference: World Congress on Osteoporosis, Osteoarthritis and Musculoskeletal Diseases (WCO-IOF-ESCEO) Location: Paris, FRANCE Date: APR 04-07, 2019
Keywords: Baker; Cyst Aspiration; Tibial Nerve Damage